2009
DOI: 10.1590/s0037-86822009000400014
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco associados à colonização por Candida spp em neonatos internados em uma Unidade de Terapia Intensiva Neonatal brasileira

Abstract: A sepse fúngica está tornando-se cada vez mais freqüente no período neonatal, especialmente nos neonatos de muito baixo peso, sendo usualmente uma condição grave que acomete preferencialmente os recém-nascidos submetidos a procedimentos invasivos e, está relacionada à elevada morbi-mortalidade 12 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…C. albicans was the commonest species (67.1%) isolated from both oral and rectal sites of infants, whereas other non-albicans Candida species accounted for one third of isolates (Table 2). It is difficult to correlate the results of this study with most other studies which have been investigated mainly the relationship between risk factors of Candida colonization and developing of Candida infections in neonates hospitalized in NICU [1,3-5,9]. However, a study in Greece has found that Candida species colonization was detected in 12.1% of neonates during a 12-month period, and C. albicans was isolated from 42% of colonized neonates.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…C. albicans was the commonest species (67.1%) isolated from both oral and rectal sites of infants, whereas other non-albicans Candida species accounted for one third of isolates (Table 2). It is difficult to correlate the results of this study with most other studies which have been investigated mainly the relationship between risk factors of Candida colonization and developing of Candida infections in neonates hospitalized in NICU [1,3-5,9]. However, a study in Greece has found that Candida species colonization was detected in 12.1% of neonates during a 12-month period, and C. albicans was isolated from 42% of colonized neonates.…”
Section: Resultsmentioning
confidence: 66%
“…In addition, candidemias were diagnosed more in colonized neonates (6.9%) as compared with 0.76% of noncolonized neonates (P = 0.002)[3]. A recent study from Brazil reported that 19% of the neonates were colonized by Candida species which were divided equally between C. albicans (50%) and non- albicans Candida (50%) [1]. The increased colonization of non- albicans Candida species as well as their cause of candidaemia in neonates and adult Jordanian patients has been shown to be similar to other studies from various countries [1,2,6,4,7,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…currently represent a serious matter for the public health, since the rates of incidence and mortality associated with these infections have revealed a considerable increase in third-level hospitals during the last decades [17][18][19] . Species of the genus Candida have been the most frequently isolated agents, which correspond to approximately 80% of the hospital-acquired fungal infections that cause death to 12% to 60% of the patients who develop candidemia [19][20][21] . The occurrence of nosocomial infections by invasive candidiasis at the Universitary Hospital of the Jundiaí Medical College during the period covered by this research was of 4% above the average described by national and international references, which report an occurrence rate of 1.49 to 6.6 cases in 1,000 hospital admissions [22][23][24][25][26] .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…14 The second most common cause of bloodstream infection in pediatric and neonatal patients admitted to intensive care units in the USA, Europe, and Latin America is fungal infections, especially by Candida spp. [13][14][15][16] In recent years, an increase in infections caused by other species of Candida non-albicans, such as Candida tropicalis, Candida glabrata, Candida krusei, Candida lusitaniae and Candida guilliermondii, has been noted. Multicenter studies conducted in Brazil have also confirmed the prevalence of species of Candida albicans and non-albicans (C. tropicalis and parapsilosis).…”
mentioning
confidence: 99%